Organizational commitment as a moderator of the effect of training on service performance: An empirical study of small to medium-sized enterprises in Malaysia - Tan, Teck-Hong *; Lim, Yong-Kean * (International Journal of Management, 2012)
This paper seeks to examine the relationship between training approaches and organizational performance among 150 service personnel from 10 Small Medium Enterprises (SEMs) in Klang Valley Malaysia. Formal training approaches used in this study are college education, formal courses run by outside providers, distance learning courses, formal in-house courses, and Internet-based courses, whereas informal training approaches are appraisal, coaching, promotion on a temporary basis, informal seminars. Regression results show that there are positive and significant relationships between both formal and informal training and service performance. When there is a presence of moderating effect of organization commitment to employees, only informal training contributes to the success of the service firm based on a higher adjusted R-square. Senior management of SMEs can benefit from this study through recognition of the role of organizational commitment to employees as a key driver to strengthen the relationship between informal training and service performances further.